Pregnancy after vasectomy: surgical reversal or assisted reproduction?. Issue 7 (17th May 2018) - Valerie, U; De Brucker, S; De Brucker, M; Vloeberghs, V; Drakopoulos, P; Santos-Ribeiro, S; Tournaye, H
Abstract: STUDY QUESTION: Should we opt for surgical vasovasostomy or IVF/ICSI after a vasectomy? SUMMARY ANSWER: Both options reveal acceptable pregnancy rates though the time to pregnancy was significantly lower in the immediate IVF/ICSI group. WHAT IS KNOWN ALREADY: About 7.4% of men regret their vasectomy and express a renewed child wish. The choice between surgical vasectomy reversal or ICSI remains difficult for patients and their fertility specialist STUDY DESIGN, SIZE, DURATION: This study was a retrospective single-center cohort analysis of all males with a vasectomy in the past seeking treatment between 2006 and 2011 ( n = 163). One group of patients opted for a reanastomosis procedure while the others opted for an immediate IVF/ICSI treatment. This included 99 males who underwent reanastomosis and 64 couples who immediately underwent ICSI treatment. PARTICIPANTS/MATERIALS, SETTING, METHODS: All reanastomosis procedures were done by the same surgeon. ICSI was used in all cases where testicular sperm were extracted by fine needle aspiration (FNA) or testicular sperm extraction (TESE). MAIN RESULTS AND THE ROLE OF CHANCE: The mean male age at vasectomy was 35.5 years and 44.4 years at reanastomosis. The mean (range) obstructive interval was 9.53 years (1–27). No significant differences were found between the two groups in female patient characteristics, such as age and parity. In the reversal group, the crude cumulative delivery rate (CDR) was 49.5%. However, in the 45 patients of this group who attempted to conceive spontaneously ('primary reanastomosis' pathway), the crude CDR was 40.0%. The remaining 54 patients (the 'switchers' pathway) who underwent a reversal procedure and later switched to ART, had a crude CDR of 57.4%. Of these, four patients opted for insemination, including two who later decided to switch to IVF/ICSI. The 64 patients who immediately underwent IVF/ICSI ('primary IVF/ICSI' pathway) had a crude CDR of 43.8% and an expected CDR of 51.6%. The difference in delivery rates between the primary reanastomosis group (40.0%) and the primary IVF/ICSI group (43.8%) was not statistically significant. Time to pregnancy was significantly shorter in the primary IVF/ICSI pathway, at 8.2 versus 16.3 months in the reanastomosis group. LIMITATIONS, REASONS FOR CAUTION: The study population was rather small. Furthermore, the study may be limited by the fact that the reason for the renewed child wish in most cases was a new relationship with another woman, a factor which may also play a role in the cause of infertility. WIDER IMPLICATIONS OF THE FINDINGS: Recanalisation of the vas seems to be a reasonable alternative for patients who do not wish to undergo immediate IVF/ICSI. In those who opt for ART immediately, the cumulative pregnancy rates seem comparable but the pregnancies occurred earlier. STUDY FUNDING, COMPETING INTEREST(S): No funding was used for this study. There is no conflict of interest for this study. TRIAL REGISTRATION NUMBER: N/A.